The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1007/s00520-019-05182-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a nutrition intervention on acute and late bowel symptoms and health-related quality of life up to 24 months post radiotherapy in patients with prostate cancer: a multicentre randomised controlled trial

Abstract: Purpose Radiotherapy to the prostate gland and pelvic lymph nodes may cause acute and late bowel symptoms and diminish quality of life. The aim was to study the effects of a nutrition intervention on bowel symptoms and health-related quality of life, compared with standard care. Methods Patients were randomised to a nutrition intervention (n = 92) aiming to replace insoluble fibres with soluble and reduce intake of lactose, or a standard care group (n = 88) who were recommended to maintain their habitual diet.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(36 citation statements)
references
References 41 publications
1
33
0
Order By: Relevance
“…Constipation as an outcome was reported in six articles. 26,27,29,31,34,36 Nil significant differences in outcomes were found in any of these studies.…”
Section: Constipationmentioning
confidence: 78%
See 4 more Smart Citations
“…Constipation as an outcome was reported in six articles. 26,27,29,31,34,36 Nil significant differences in outcomes were found in any of these studies.…”
Section: Constipationmentioning
confidence: 78%
“…The EORTC QLQ-C30 and the site-specific modules PR25, CX24 and EN-24 were used in seven articles (six studies) to assess individual GI toxicities and overall QOL scores. 5,26,27,29,31,34,36 Ravasco et al reported a significant improvement in median QOL function scores within the individual DC group at RT completion (P < 0.002). 27 These improvements were proportional to increases in intake of energy and protein, and nutritional status improvement (P < 0.05).…”
Section: Quality Of Lifementioning
confidence: 98%
See 3 more Smart Citations